CHARACTERIZATION OF CARBONATE RESERVOIRS IN THE KUJUNG FORMATION, - Fauzan Siregar, Imam
The "GORGA" field is located in the East Java Basin, which is a back arc basin and parallel to the mountains in the south of Java Island. This research focuses on one of the formations in the East Java Basin, namely the Kujung I Formation with carbonate lithology. Analysis of well log data shows that AI and Vp/Vs ratio are sensitive elastic parameters. The linear programming sparse spike (LPSS) inversion seismic method was carried out in AI and extended elastic impedance analysis for the Vp/Vs ratio. The results of elastic parameter inversion will generally be biased towards AI-VpVs ratio values that are not dominant and the data relationship is linear when cross plotting, while petrophysical parameters have a nonlinear trend, therefore curved pseudo elastic impedance (CPEI) and pseudo elastic impedance (CPEI) attribute approaches are used - lithology (PEI-L). Reservoir characterization is carried out using the petrophysical parameter approach to be analyzed, namely porosity via the PEI-L attribute to view the compaction trend and water saturation via the CPEI attribute to view the fluid trend. CPEI and PEI-L attributes were created using trigonometric approximation and maximum correlation angle analysis of the target petrophysical parameters. The correlation of CPEI with water saturation in the IF-2 well is 0.6511 and in the IF-4 well is 0.7464. The correlation of PEI-L with porosity in the IF-2 well is - 0.7906 and in the IF-4 well is -0.8981. The results of the CPEI attribute and PEI-L attribute are transformed into volume porosity and water saturation. The research results show low values of AI, VpVs ratio, CPEI, PEI-L, and water saturation, as well as high porosity, indicating that the "GORGA" field in the Kujung I Formation is a potential porous carbonate reservoir and is indicated to be filled with hydrocarbon fluids